Mr. Holland's opus - Dreyfuss, Richard; Headly, Glenne; Thomas, Jay, 1948-2017.; Macy, William H., 1950-; Witt, Alicia; Kelly, Jean Louisa; Dukakis, Olympia; Duncan, Patrick Sheane; Cort, Robert W.; Herek, Stephen; Hollywood Pictures Home Video (Firm); Buena Vista Home Entertainment (Firm); et al. (Burbank, CA : Hollywood Pictures Home Video : Distributed by Buena Vista Home Entertainment, 1995)
The story of a serious musician who reluctantly enters the teaching profession to remain afloat financially and discovers that his true passion is teaching.
Program start -- Opening credits -- Inauspicious beginning -- Free time -- Off-key -- A poor compass -- Connective tissue -- Not just notes on a page -- Cirriculum in question -- New Assignment -- Challenged -- Terrible news -- A mother's despair -- A momento -- Domestic discord -- Free advise -- Late night rehearsal -- A proposition -- At the bus depot -- Angry son -- A personal dedication -- An apology for the arts -- Surprise -- A symphony -- End credits.
Originally produced as a motion picture in 1995.
Includes production featurette.
Director of photography, Oliver Wood ; edited by Trudy Ship ; music by Michael Kamen.
Richard Dreyfuss, Glenne Headly, Jay Thomas, W.H. Macy, Alicia Witt, Jean Louisa Kelly, Olympia Dukakis.
MPAA rating: PG.
DVD; Dolby digital 5.1 surround; region 1.
Keywords: Music teachers -- Drama; Teacher-student relationships -- Drama; Fathers and sons -- Drama; Teaching -- Drama; Feature films